food-science 2018
DOI: 10.35841/food-science.1.1.33-47
|View full text |Cite
|
Sign up to set email alerts
|

Children's nutritional status and its determinants in small towns, Sebeta Hawas district, Oromia, Ethiopia.

Abstract: Research Article pregnancy and lactation. Women are typically the main caretakers of children after birth, and in order to provide quality care they need continued adequate food consumption and health care, rest, and measures to protect their mental health, such as protection from abuse. The third underlying determinant, health environment and services, conditions children's exposure to pathogens and the use of preventative and curative health care. Elements of a health environment include access to safe water… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 6 publications
7
8
0
Order By: Relevance
“…This study further identified that children with higher birth order had higher odds of acute malnutrition than those children with lower birth order. This is icontrary to other studies in Ethiopia 21,24 but confirms the findings of studies in South Asian countries such as Bangladesh, India, the Maldives, Nepal, Pakistan, and Afghanistan. 15,22,25 The explanation for this might be due to cultural practices in this study area which gives more emphasis to relatively older siblings who stopped breastfeeding and complaint on family about food than the younger one still breastfeeding which might result in less time for feeding and care of younger children.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…This study further identified that children with higher birth order had higher odds of acute malnutrition than those children with lower birth order. This is icontrary to other studies in Ethiopia 21,24 but confirms the findings of studies in South Asian countries such as Bangladesh, India, the Maldives, Nepal, Pakistan, and Afghanistan. 15,22,25 The explanation for this might be due to cultural practices in this study area which gives more emphasis to relatively older siblings who stopped breastfeeding and complaint on family about food than the younger one still breastfeeding which might result in less time for feeding and care of younger children.…”
Section: Discussionsupporting
confidence: 90%
“…[14][15][16] It is also in line with findings of other studies in Ethiopia. [17][18][19][20][21] This might be due to the fact that mothers with formal education acquire knowledge which helps them to understand and obtain information on optimal child feeding and care practice through education, advice and media.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The other factor significantly associated with wasting was the family size. Children from smaller family sizes were 87% (AOR: 0.13, 95% CI (0.09, .21)) less likely to develop wasting like a study conducted in Jimma Zone, Southwest, Ethiopia [31] and Sebeta, Hawas District, Oromia, Ethiopia [32]. The possible reasons may be due to large family size with low socioeconomic status, which leads to inadequate intake, monotonous diet, a diet with poor nutrient density, inappropriate feeding practices, lack of hygienic practices, and illness.…”
Section: Discussionmentioning
confidence: 81%
“…It is also an indicator of child survival. Malnutrition is a major public health problem that affects most people in developing countries and occurs prominently among children under five years of age (Haile and Amboma, 2018). Adequate nutrition is essential in early childhood to ensure healthy growth, proper organ formation and function, a strong immune system and neurological and cognitive development.…”
Section: Back Ground Informationmentioning
confidence: 99%